2016
DOI: 10.1111/iju.13114
|View full text |Cite
|
Sign up to set email alerts
|

Optimum anesthesia for reliable urethral pressure profilometry in female dogs and goats

Abstract: Abbreviations & Acronyms C r = repeatability coefficient C RR = coefficient of reproducibility between occasions CV within = within-subject coefficient of variation FA = functional area FUL = functional urethral length MUCP = maximal urethral closure pressure NS = not significant S w = within-subject standard deviation UPP = urethral pressure profilometry Objectives: To investigate the effects of propofol and isoflurane on urethral pressure profilometry of female dogs and goats, and to identify the method of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The static UPP was determined on animals placed in sternal recumbency. The measurements were carried out during recovery from propofol action in a state of light anesthesia (palpebral reflex present) as our group has previously shown that this kind of anesthesia only moderately affects the UPP measurements [ 17 ]. A twin-lumen catheter (6Fr, Laborie) with side holes was withdrawn from the bladder and the urethra at a constant speed of 2.5 mm/s.…”
Section: Methodsmentioning
confidence: 99%
“…The static UPP was determined on animals placed in sternal recumbency. The measurements were carried out during recovery from propofol action in a state of light anesthesia (palpebral reflex present) as our group has previously shown that this kind of anesthesia only moderately affects the UPP measurements [ 17 ]. A twin-lumen catheter (6Fr, Laborie) with side holes was withdrawn from the bladder and the urethra at a constant speed of 2.5 mm/s.…”
Section: Methodsmentioning
confidence: 99%
“…Although these animals have not been previously used for testing of intraurethral cell therapy, we have demonstrated that caprine female urethra and EUS have similar parameters to those reported in women . Our group has experience in working with pigs and dogs, and we postulate that goats are the most adequate large experimental quadreped animals for testing of intraurethral manipulations. An interesting alternative could be minipigs used by Amend et al but the porcine female urethra (even in minipigs) is much longer than in humans, which creates different conditions for needle insertion both in peri‐ and transurethral injections.…”
Section: Discussionmentioning
confidence: 69%
“…Static urethral pressure profilometry was performed on animals placed in a sternal recumbency restraint during recovery from propofol sedation in a way described previously by our group . The parameters which were important for transplantation procedure were 1) the functional urethral length (FUL) and 2) the distance from the beginning of UPP to maximal urethral closure pressure (MUCP) point as a percentage of FUL which corresponded to the location of maximal EUS strength in the longitudinal axis of the analyzed urethra.…”
Section: Methodsmentioning
confidence: 99%
“…Urinary continence is therefore partially under somatic neuronal control. When determining incontinence by measuring the urethral wall pressure in animals in sedation versus deep anesthesia, significant differences were noted disclosing the contribution of the neuronal control and striated muscles to the overall closure pressure [ 36 ]. The contribution of passive forces such as tissue tension, blood pressure to the overall continence is noticed, when urodynamics are measured in animals in anesthesia and upon sacrifice (unpublished observation).…”
Section: Large Animal Models To Study Urinary Incontinencementioning
confidence: 99%